Evaluation of 'Stop Smoking in its Tracks': an intensive smoking cessation program for pregnant Aboriginal women incorporating contingency-based financial rewards - Megan E Passey; Janelle M Stirling (Sax Institute, 2018)
Background: Smoking during pregnancy is three times as common among Aboriginal women as non-Aboriginal women, with consequent higher rates of adverse health outcomes. Effective interventions to support Aboriginal women to quit smoking have not yet been identified. Objectives: To assess the feasibility and acceptability of implementing a culturally tailored, intensive smoking cessation program, including contingency-based financial rewards (CBFR), for pregnant Aboriginal women. Methods: The structured program included frequent support with individually tailored counselling, free nicotine replacement therapy, engagement with household members, specially developed resources, CBFR and peer support groups. It was implemented by three rural Aboriginal Maternal and Infant Health Services sites. Women were eligible if they or their partner were Aboriginal; and if they were: current smokers or had quit since becoming pregnant; ≥16 years old; at <20 weeks gestation; and locally resident. Data included demographics, obstetrics, initial smoking behaviour, program implementation and quitting behaviour. Self-reported quitting was confirmed by expired carbon monoxide (CO). Women and staff were interviewed about their experiences. Results: Twenty-two of 38 eligible women (58%) enrolled in the program, with 19 (86%) remaining at the end of their pregnancy. The program was highly acceptable to both women and providers. Feasibility issues included challenges providing twice-weekly visits for 3 weeks and running fortnightly support groups. Of the 19 women who completed the program, 15 (79%) reported a quit attempt lasting ≥24 hours, and 8 (42%) were CO-confirmed as not smoking in late pregnancy. The rewards were perceived to help motivate women, but the key to successful quitting was considered to be the intensive support provided. Conclusions: 'Stop Smoking in its Tracks' was acceptable and is likely to be feasible to implement with some modifications. The program should be tested in a larger study.